The Role of Memory in Helping Children Learn Grammar Independently: A Library Research - Finasyifa Afidah; Iqna Mayzatus Shima; Buntara Adi Purwanto (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2026)
Grammar acquisition is a crucial component of children's language development that involves complex cognitive processes. This library research investigates the contribution of memory systems, particularly working memory and long-term memory, to children's independent grammar learning. Employing a qualitative descriptive approach, the study synthesizes findings from books, scholarly journal articles, and previous research to examine how working memory facilitates the processing of complex grammatical structures, how declarative and procedural long-term memory support the storage and automatization of grammatical knowledge, and how memory-based learning strategies encourage autonomous learning. The findings reveal that working memory capacity plays an essential role in enabling children to process complex grammatical patterns, whereas long-term memory, especially procedural memory, contributes to the automatic use of grammar through repeated exposure and active encoding. Strategies such as repetition, categorization, visual imagery, and retrieval practice are identified as valuable approaches for strengthening children's independent grammar learning, although their effectiveness is influenced by the quality of the encoding process. Overall, this study contributes to psycholinguistic research while providing practical insights for developing independent learning materials that accommodate children's cognitive and memory capacities.